Effect of enhanced homestead food production and aquaculture on dietary intakes of women and children in rural Cambodia: A cluster randomized controlled trial. Issue 3 (5th January 2018) - Verbowski, Vashti; Talukder, Zaman; Hou, Kroeun; Sok Hoing, Ly; Michaux, Kristina; Anderson, Victoria; Gibson, Rosalind; Li, Kathy H.; Lynd, Larry D.; McLean, Judy; Green, Tim J.; Barr, Susan I.
Abstract: The Cambodian diet is low in nutrient‐dense animal‐source foods. Enhanced homestead food production (EHFP) and aquaculture, which increase availability of nutrient‐dense foods, are promising interventions to improve dietary intake. This study examined the effect of EHFP with or without aquaculture on dietary intake and prevalence of inadequate intake of select nutrients among women and children living in rural Cambodia, compared to controls. In a registered, cluster randomized controlled trial in Prey Veng, Cambodia, 10 households in each of 90 villages ( n = 900) were randomized by village to receive EHFP, EHFP plus aquaculture, or control. After 22‐month intervention, 24‐hr dietary recalls (24HRs) were collected from mothers aged 18–50 years ( n = 429) and their children aged 6 months–7 years ( n = 421), reported by their mothers. Usual intake distributions (generated using 24HRs and repeat 24HRs on a subsample) were used to estimate prevalence of inadequate intake. Compared to controls, women in the EHFP group had significantly higher zinc (+1.0 mg/d) and Vitamin A (+139 retinol activity equivalents/d) intakes, and women in the EHFP plus aquaculture group had significantly higher iron (+2.7 mg/d), Vitamin A (+191 retinol activity equivalents/d), and riboflavin (+0.17 mg/d) intakes. Women in the EHFP plus aquaculture group also had significantly lower prevalence of inadequate iron (−7%, at 10% bioavailability), Vitamin A (−19%), and riboflavin (−17%) intakes, compared to controls. No significant differences in intakes or nutrient adequacy were observed among children or between EHFP and EHFP plus aquaculture groups. The biological importance of the small differences in nutrient intakes among women remains to be established.